Evaluating risk factors for surgical site infections following open reduction and internal fixation surgery for ankle fractures: a systematic review and meta-analysis - Feifan Luan; Cong Zheng; Yuzhong Zheng; Jiayi Chen; Yurui Wu; Chenxiao Zheng (Frontiers in Public Health, 2025)
BackgroundAnkle fractures are common injuries requiring surgical intervention, specifically open reduction and internal fixation (ORIF), which carries a risk of surgical site infections (SSIs). Identifying and understanding the risk factors associated with SSIs in these patients is crucial for improving surgical outcomes and patient care.MethodsThis systematic review and meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We searched PubMed, Embase, Web of Science, and the Cochrane Library on September 19, 2023, without restrictions on publication period or language. The inclusion criteria comprised observational studies and randomized controlled trials that investigated risk factors for SSIs following ORIF for ankle fractures. Exclusion criteria included non-empirical studies, studies without specific outcomes on SSIs, non-ORIF surgeries, and studies with incomplete data. The quality of included studies was assessed using the Newcastle-Ottawa Scale (NOS), and statistical analyses were performed using Stata 17.ResultsOut of 1,255 initially identified articles, eight studies met the inclusion criteria after deduplication, screening, and full-text review. These studies highlighted several risk factors for SSIs, including diabetes, open fractures, high-energy injuries, and smoking, with diabetes and open fractures significantly increasing the risk. Antibiotic prophylaxis emerged as a protective factor. The quality assessment revealed a high standard of research quality among the included studies, and sensitivity analysis confirmed the robustness of the findings.ConclusionThis meta-analysis underscores the importance of recognizing diabetes, open fractures, high-energy injuries, smoking, and a BMI exceeding 30 as significant risk factors for SSIs following ORIF for ankle fractures. The administration of antibiotic prophylaxis serves as a protective measure. Healthcare providers should incorporate strategies to mitigate these risks, enhancing postoperative care and reducing the incidence of surgical site infections.